2022
DOI: 10.26803/ijlter.21.10.5
|View full text |Cite
|
Sign up to set email alerts
|

Academic Dishonesty and the Diamond Fraud: Attitudes of UAE Undergraduate Business Students during the COVID-19 Pandemic

Abstract: This paper examines academic dishonesty by business undergraduate students in the United Arab Emirates, using the lens of the fraud diamond theory, during the Covid-19 pandemic. The study used a survey of 305 students from the college of business in a major public university in the UAE, from August 2020 to November 2020 to investigate the extent of academic dishonesty. Results revealed H1 (p<0.001; p-value=0.73), H2 (p<0.001; p-value=0.52), H3 (p<0.001; p-value=0.76), and H4 (p<0.001; p-value=0.53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Therefore, it can be concluded that pressure has a positive and significant influence on the tendency to commit academic dishonesty. The results in this study are in line with research conducted by Albrecht, (2012), Becker et al, (2006), Munirah and Nurkhin, (2018), Warni and Margunani, (2022), Al Serhan et al, (2022) which states that pressure has a significant and positive relationship to academic dishonesty. Based on research results, students commit academic dishonesty due to financial pressure, pressure because they do not understand the material, environmental pressure to cheat and pressure to always get good grades.…”
Section: The Influence Of Pressure On Academic Dishonesty Behaviorsupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, it can be concluded that pressure has a positive and significant influence on the tendency to commit academic dishonesty. The results in this study are in line with research conducted by Albrecht, (2012), Becker et al, (2006), Munirah and Nurkhin, (2018), Warni and Margunani, (2022), Al Serhan et al, (2022) which states that pressure has a significant and positive relationship to academic dishonesty. Based on research results, students commit academic dishonesty due to financial pressure, pressure because they do not understand the material, environmental pressure to cheat and pressure to always get good grades.…”
Section: The Influence Of Pressure On Academic Dishonesty Behaviorsupporting
confidence: 92%
“…Thus, it can be concluded that rationalization has a significant positive influence on academic cheating behavior. The results in this study are in line with research conducted by Albrecht, (2012), Becker et al, (2006), Munirah and Nurkhin, (2018), Warni and Margunani, (2022), Al Serhan et al, (2022) .000 rationalization has a significant and positive relationship with academic dishonesty. Based on research results, students commit academic dishonesty because they rationalize that all their actions are correct with the reason of getting good grades, seeing other people also cheating, as a form of solidarity, not being interested in the material, assuming there are no victims.…”
Section: The Influence Of Rationalization On Academic Dishonesty Beha...supporting
confidence: 91%
See 1 more Smart Citation
“…Although universities use software programmes that detect plagiarism to align with current trends and needs, they are ineffective with CC (Singh and Remenyi 2016). Aljanahi et al International Journal for Educational Integrity (2024) 20:9 Recent studies have shed light on academic integrity and CC in the UAE in particular (e.g., Al Serhan et al 2022;Khan et al 2019;Khan et al 2020;Pacino 2021;Rogers 2019). However, these studies mostly tackled students' perceptions of CC as well as service providers like essay mills, rather than investigating faculty perceptions.…”
Section: How Do Faculty and Institutions Minimise Contract Cheating?mentioning
confidence: 99%
“…Dishonest behavior in the academic context is an important issue faced by educational institutions worldwide [5][6][7], as a widespread phenomenon [8] and increase [9,10], which occurs from primary schools to higher education institutions, and it is currently receiving increasing global attention [11]. Academic dishonesty remains a prominent research issue in various countries, including China.…”
Section: Introductionmentioning
confidence: 99%